A fellebbezés elintézése a harmadfokú büntetőeljárásban - Törő, Blanka; Háger, Tamás (Debreceni Jogi Műhely, 2013)
The questions of remedy are in close relations with the legal force. The legal force of theclinching decisions represents the final, irreversible decision about the demand of penal law,which decision is a guideline and undeniably binding for all, and cannot be attacked with anordinary appeal.The legal force of other decisions with the capacity to have legal force defines a decisionwhich is final, irreversible, a guideline for all, obligatory (independent of executability) andcannot be attacked with an appeal.Furthermore, there are the decisions with formal legal force, the legal force of which standsonly for not being appealable.A valid decision can only be made about the factual and legal basis of criminal responsibilityby the court that is entitled and obligated to do it, that is, only the court has a right duringcriminal procedure to decide whether there was a crime or not, and if yes, who committed it.In relation to this, the question of material legal force can only regard the constituted chargeand the act in consideration, when the court makes a permanent decision about the demand ofpenal law, in the framework of the substantive judging of the act that became the object ofprosecution.Lodging an appeal on legal grounds shall be governed by the provisions set forth in ChapterXV of the Criminal procedure Act. The judgement of the court of second instance may beappealed at the court of appeal. The appeal against the judgement of the court of secondinstance may involve any of the dispositions therein or exclusively the justification thereof.An appeal may be lodged for legal or factual reasons. An appeal suspends the part of the judgement to become final which is to be reviewed by the court of appeal owing to the appeal.The third remedy is allowed only in cases where the first and second instance decision isabsolutely different in the question of guilty.